Intussusception in an infant as a manifestation of COVID-19 - Zorays Moazzam; Areej Salim; Alina Ashraf; Fyezah Jehan; Muhammad Arshad (Elsevier, 2020)
Gastrointestinal manifestations of COVID-19 are rare and have primarily been limited to diarrhea or vomiting. Intussusception is the most common cause of bowel obstruction in infants, with up to 30% of pediatric intussusception cases having a preceding viral illness. We present the rare case of intussusception in a SARS-CoV-2 positive infant. This is the first documented case of survival in a SARS-CoV-2 positive patient presenting with intussusception as the primary manifestation. As our knowledge of this disease evolves, surgeons need to remain suspicious for possible gastrointestinal manifestations of COVID-19.